Pengaruh Supervisi Akademik Pengawas Sekolah dan Profesionalisme Guru terhadap Mutu Pendidikan Pada SD di Kota Kendari - Raehang, Raehang; Rahmawati, Rahmawati (Institut Agama Islam Negeri Kendari, 2022)
This survey research aims to determine (1) the impact of academic supervision by school inspectors on teacher professionalism, (2) the influence of academic supervision by school inspectors on the quality of education, (3) the effect of teacher professionalism on the quality of education, and (4) the combined influence of academic supervision by school inspectors and teacher professionalism on the quality of education in elementary schools in Kendari City. The study focused on a sample of 27 elementary school teachers in Kendari City. The research instrument was a questionnaire that has been validated and proven reliable. The data analysis techniques included descriptive and inferential analysis. The results of this study found that: 1) Academic supervision by school inspectors has no significant partial effect on teacher professionalism, (2) Academic supervision by school inspectors directly affects the quality of elementary education in Kendari City, (3) Teacher professionalism significantly impacts the quality of elementary education in Kendari City, and (4) academic supervision by school inspectors and teacher professionalism together influence the quality of elementary education in Kendari City by 36.1%, while the remaining 63.9% is influenced or explained by other factors not discussed in this study.Keywords: Academic supervision of school supervisors, teacher professionalism, education quality